Implementasi Dan Pengembangan Dashboard Akademik Feeder PDDikti Dengan Data Mart: Studi Kasus Universitas Dinamika Bangsa - Rahim, Abdul; Wardani, Muhammad; Alam Jusia, Pareza; Siswanto, Agus (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2025)
Reporting academic data to the Pangkalan Data Pendidikan Tinggi (PDDIKTI) is a mandatory requirement for higher education institutions to ensure the validity and synchronization of student, lecturer, course, and academic activity data. However, in practice, several challenges arise, such as discrepancies between the internal academic system (Siakad) and the Feeder PDDIKTI, delays in reporting, and difficulties in monitoring synchronization status in real-time. This study aims to develop an academic data reporting monitoring dashboard based on a Data Mart, enabling efficient and centralized monitoring of academic data synchronization. The dashboard integrates data from Feeder PDDIKTI and Siakad through the Extract, Transform, Load (ETL) process to generate accurate and easily interpretable information. The findings indicate that the developed dashboard effectively visualizes academic data synchronization status in real-time, reduces reporting errors, and accelerates the validation process before submission to PDDIKTI. Thus, this dashboard serves as an effective solution to support academic data governance in higher education institutions